Chronic cluster headache: A study of the telencephalic and cerebellar cortical thickness. (May 2022) - Demichelis, Greta; Pinardi, Chiara; Giani, Luca; Medina, Jean Paul; Gianeri, Ruben; Bruzzone, Maria Grazia; Becker, Benjamin; Proietti, Alberto; Leone, Massimo; Chiapparini, Luisa; Ferraro, Stefania; Nigri, Anna
Abstract: Purpose: Previous studies on brain morphological alterations in chronic cluster headache revealed inconsistent findings. Method: The present cross-sectional explorative study determined telencephalic and cerebellar cortex thickness alterations in a relatively wide sample of chronic cluster headache patients (n = 28) comparing them to matched healthy individuals. Results: The combination of two highly robust state-of-the-art approaches for thickness estimation (Freesurfer, CERES), strengthened by functional characterization of the identified abnormal regions, revealed four main results: chronic cluster headache patients show 1) cortical thinning in the right middle cingulate cortex, left posterior insula, and anterior cerebellar lobe, regions involved in nociception's sensory and sensory-motor aspects and possibly in autonomic functions; 2) cortical thinning in the left anterior superior temporal sulcus and the left collateral/lingual sulcus, suggesting neuroplastic maladaptation in areas possibly involved in social cognition, which may promote psychiatric comorbidity; 3) abnormal functional connectivity among some of these identified telencephalic areas; 4) the identified telencephalic areas of cortical thinning present robust interaction, as indicated by the functional connectivity results, with the left posterior insula possibly playing a pivotal role. Conclusion: The reported results constitute a coherent and robust picture of the chronic cluster headache brain. Our study paves the way for hypothesis-driven studies that might impact our understanding of the pathophysiology of this condition.